Pendampingan Guru Pendamping Khusus untuk Meningkatkan Kompetensi Pengelolaan dan Penanganan Perilaku pada Anak Berkebutuhan Khusus - Fitriatun, Erna; Muliyani, Sri Erny; Susilawati, Indri; Mulyajaya, Muhammad Satria; Sukarman, Sukarman (Insan Kreasi Media, 2025)
This article examines a mentoring program for Special Education Support Teachers (Guru Pendamping Khusus / GPK) aimed at improving competencies in behavior management and intervention for Children with Special Needs (CSN) at Buah Hati Learning Center in Mataram. The mentoring program focuses on strengthening GPKs’ practical skills in implementing effective, consistent, and scientifically grounded behavioral intervention strategies. The program seeks to enhance GPKs’ capacity to understand the behavioral characteristics of CSN, conduct systematic behavioral observations, analyze behavioral triggers, and apply positive behavior intervention strategies, while simultaneously reinforcing behavior management systems at the institutional level. The mentoring was implemented using a Participatory Action Research (PAR) approach, encompassing stages of needs identification, action planning, conceptual training, individual coaching, structured observation, and collaborative reflection. Data were collected through interviews, observations, field notes, and documentation of classroom practices. The results indicate a significant improvement in GPK competencies, particularly in the application of positive reinforcement, ABC (Antecedent–Behavior–Consequence) behavioral analysis, management of challenging behaviors, and the development of individualized behavior intervention plans. Positive impacts were also observed among CSN, including a reduction in maladaptive behaviors, improved ability to follow instructions, and the creation of a more conducive learning environment. At the institutional level, the program generated strategic recommendations, including the development of standard operating procedures (SOPs) for behavior management, strengthened supervision mechanisms, and the creation of internal behavior management modules.